Quelques réflexions sur les sociétés insulaires du Pacifique - Christian Huetz de Lemps (EchoGéo, 2011)
With regard to young insular states in the Pacific ocean, History is responsible for weakness and instability, but Joel Bonnemaison’s research shows how important is to consider the cultural bottoms of these very old civilizations.